River Odra Estuary (North-West Poland): Assessment of Physical and Chemical Parameters of Water on Basis of European Union Water Framework Directive - Daniszewski, Piotr (Asian Journal of Chemistry, 2014)
This paper presents the evaluation of physico-chemical parameters of water river Odra Estuary based on the European union water framework directive. Water is a necessary element for endurance of living on earth, which contains minerals, essential for human being as well as for earth and aquatic life. Lakes have long been at the center of human attention. To address the increasing degradation of surface waters in the European union, the approach to the evaluation and protection of water resources was changed. This approach was formulated in the European union water framework directive (2000/60/EC), which calls for the protection of water, as well as an environment-friendly and comprehensive approach to water assessment. The Odra Estuary includes, as its major part, the brackish Szczecin Lagoon which consists of two parts: the Kleines Haff (located in Germany) and the Wielki Zalew located in Poland. The Lagoon receives the river Odra water supplied from the south; prior to being discharged into the Lagoon, part of the Odra flow passes through Lake Dabie. The Odra (German: Oder) estuary is located at the southern Baltic sea (German-Polish border). It consists of the Szczecin Lagoon and the Pomeranian Bay. The Szczecin Lagoon (687 km2) can be subdivided into the "Large Lagoon" (Polish: Wielki Zalew) on the polish territory and the "Small Lagoon" (German: Kleines Haff) on the German side. The Lagoon is connected to the Pomeranian Bay via 3 outlets. The research was carried out in the years 2008-2012, between april and october. From each of the three measuring stations located in the water river Odra estuary included the study, two separate water samples were taken for chemical analysis. The studied water river Odra Estuary had pH values in the neutral range 7.76 to 7.89. According to the classification of the European union water framework directive, all water were classified as first class. The tests have demonstrated that water quality in the water Szczecin Lagoon with regard to the tested indicators varied. By analyzing the average annual values, one can note that the pH, O2diss and NO3- concentration showed a relatively small variation in all the investigated water. The total suspended solids in the river Odra Estuary, fell into the II class. The Ptot. concentrations in the surface layer of the water river Odra estuary was little differentiated, reaching the levels appropriate for the III quality class according to the classification of the European union water framework directive. The total phosphorus concentration was 0.48-0.69 mgP dm-3. The concentrations of PO43-diss in the tested waters varied more significantly-corresponding to water quality classes ranging from IV. The concentrations saturation with O2 was 42.9-96.3 %. In the case of nitrogen compounds, nitrates and nitrites values for these indicators fell into the I and II class in all the surveyed water river Odra Estuary in accordance with the classification of the European union water framework directive. The indicator which proves high productivity of the water is the biochemical oxygen demand (BOD5). The level of this indicator in the studied river Odra estuary was at level III. The highest concentration of oxygen in the waters was found in the river Odra Estuary (about 8.3 mg O2 dm-3). In the remaining water oxygen levels were similar (still in I class). National sanitation foundation water quality index (NSF WQI) used for rating of water quality in river Odra estuary indicates that the quality of water is slightly polluted (WQI = 51.4).